Kejadian Stunting Pada Balita - Nurharlinah Nurharlinah; Rosnani Rosnani; Ari Athiutama; Enisah Enisah (PT.Mantaya Idea Batara, 2024)
Until now, stunting remains a global issue, as evidenced by its high prevalence rate of 21.9%. Stunting occurs in children and is characterized by a discrepancy between age and height, resulting from chronic malnutrition, ultimately hindering the physical and cognitive development of the child. This research aims to understand the prevalence of stunting in the Puskesmas Palemraya Service Area in Ogan Ilir Regency. It is a quantitative study using a descriptive approach with 655 respondents selected through total sampling techniques. Anthropometric measurements were taken to assess height, and birthdates were recorded in the Maternal and Child Health Book. Univariate data analysis was conducted to observe the frequency distribution of each variable. The research findings indicate that the majority of respondents were male (52.06%), aged 24- 59 months (61.53%), and the majority did not experience stunting (94.66%). The research concludes that 5.34% of children in the Puskesmas Palemraya Primary Service Area in Ogan Ilir Regency suffer from stunting, meeting the government's target for reducing stunting by 14%.